E-Procurement in Malaysian Construction: Benefits and Challenges in Implementation - Mohd Nasrun Mohd Nawi; Rafikullah Deraman; Jibril Adewale Bamgbade; Faisal Zulhumadi; Salman Riazi Mehdi Riazi (International Journal of Supply Chain Management, 2017)
In this paper, the benefits and challenges embedded in Electronic procurement (e-procurement) are highlighted. Specifically, the benefits of introducing e-procurement (termed e-Perolehan) for tendering and online registration of businesses and companies in Malaysia was emphasized. This study also focus on the advantages of E-procurement adoption such as cost reduction, improved efficiency in government business with the aid of internet-based information and communication technology. The study concluded with recommendations to policy makers to pay more attention to the availability of infrastructure such as information technology for a better E-procurement implementation.